Implementation Education Study Of Work Motivation and Work Environment in Enhancing Employee Performance Surabaya City Electoral Commission - Ririn Frebianti; Iriani Ismail (Universitas Muhammadiyah Enrekang, 2023)
This research is motivated by the fluctuating employee performance of the Surabaya City Electoral Commission (KPU) that does not synergize with the working motivation and work environment conditions of the Surabaya City KPU employees. The aim of this study is to determine the influence of (1) work motivation on performance, (2) work environment on performance, (3) work motivation and work environment simultaneously on performance, and (4) work motivation as the dominant variable affecting performance. The data used in this study were obtained from observations and questionnaires using random sampling methods. The questionnaire values were disclosed using a Likert scale ranging from 1 to 5. The analytical methods used in this research are t-test analysis, F-test analysis, and multiple linear regression analysis. The results of this research indicate that (1) work motivation has a positive and significant influence on performance, (2) work environment has a positive and significant influence on performance, (3) work motivation and work environment simultaneously have a positive and significant influence on performance, and (4) work motivation is the dominant variable among the two variables influencing performance.